Editorial Statistics - Pagano, Marco; Zechner, Josef (Review of Finance, 2007)
The following statistics are based on all submissions and resubmissions receivd in the period from January 1st, 2006 to December 31st, 2006. The turnaround time is the number of days elapsed from receipt of the manuscript to notification of the editorial decision. The first response time is the number of days elapsed from initial receipt of the manuscript to notification of the first editorial decision.